From Betel Nut Trader to Successful Entrepreneur in Bireuen Regency: Biography of H. Saifannur (1956-2020) - Cahaya, Putri Kilan; Zulfan, Zulfan; Alfian, Alfian (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
Betel nut is an important commodity for farmers in Bireuen Regency, with their income highly dependent on the betel nut harvest. One of the famous betel nut traders in Bireuen Regency is H. Saifannur, who has made a major contribution to the development of betel nut farming in this area. This study aims to: (1) describe the background of H. Saifannur's life, (2) reveal H. Saifannur's journey to becoming a betel nut trader in Bireuen Regency, (3) trace H. Saifannur's career in other business sectors, and (4) explain the relationship between H. Saifannur's career as an entrepreneur and entering the world of politics. This study uses a qualitative approach with a historical method, with primary data sources in the form of interviews with informants, and secondary data from literature studies. Data collection techniques include interviews, documentation, literature studies, and data analysis. The results of the study concluded that: (1) H. Saifannur, S.Sos is an experienced politician and entrepreneur in various fields, (2) he served as the Regent of Bireuen in 2017-2020 and tried to improve the community's economy, even though his betel nut business did not run smoothly.